Interaction of surface-attached haemoglobin with hydrophobic anions monitored by on-line acoustic wave detector - Ellis, J.; Xu, S.; Wang, X.; Herzog, G.; Arrigan, Damien; Thompson, M. (Elsevier, 2010)
The behaviour of proteins on surfaces and at interfaces is an important field with applications in drugdevelopment, clinical diagnostics and studies of device biocompatibility. A key factor is the conformation ofsurface-bound proteins, which can affect chemical signalling and drug binding. A recent study of theinteractions of haemoglobin with hydrophobic anions at a liquid–liquid interface has shown that a pH- andorientation-dependent conformational change occurs in the haemoglobin molecule upon interaction withthese anions. To corroborate these results, we use an acoustic wave detector to study binding of solutionphase hydrophobic anions to surface-adhered haemoglobin. The orientation of protein is controlled by thiol chemistry, which generates hydrophilic and hydrophobic surfaces. Tetraphenylborate-based anions are introduced to the haemoglobin coated surface via an on-line flow-injection system to monitor the signal in real-time. Changes in the acoustic properties of the surface, measured piezoelectrically, are related to interactions between the protein and the anions. Signal strength is proportional to the degree of interaction between the salts and the haemoglobin, which in turn, is influenced by its conformation.